출산율 개선을 위한 관련법 연구 - 김태동(Kim Tae Dong) (사회복지법제연구, 2017)
우리나라 여성의 합계출산율은 2016년 1.17명으로 OECD 가입국 중 가장 낮은 통계수치이다. 이러한 출산율의 감소는 생산인구의 감소, 국가 성장에 악영향을 준다. 이에 다음과 같은 개선점을 고려해야 한다. 첫째, 현행 육아휴직의 1년 이내인 기간에 대한 조정이 필요하다. 육아휴직 기간을 공무원 수준으로 증가할 필요가 있다. 또한 육아휴직을 사용할 때 별도의 신청없이 자동적으로 육아휴직을 사용할 수 있도록 개정할 필요가 있다. 둘째, 휴직에 대한 소득대체율의 인상이 매우 절실한 상황이다. 현재 근로자의 소득대체율은 고용보험법 제95조에 의하여 40%이다. 그러나 40%의 소득대체율로는 육아휴직을 사용하는 유인제도로서 매우 미흡하다. 높은 소득대체율은 출산율 상승에 큰 요인이 되므로 소득대체율을 단계적으로 인상하는 고용보험법 개정이 필요하다. 또한 상한액과 하한액에 대한 조정도 동시에 개선해야 출산율에 긍정적으로 영향을 미칠 수 있을 것이다. 셋째, 소득대체율을 인상하는 법개정에 따라 재원확보를 고려해야한다. 우리나라의 경우는 고용보험에서 육아휴직급여가 지원되고 있다. 실업급여는 본래 취지대로 실업자 구제 목적을 위하여 사용하여야 하고, 실직급여, 출산전후휴가급여, 육아휴직급여의 재편성을 고려해야 하며, 재원에 대한 국가의 적극적인 지원을 통한 출산율 개선이 절실하다. The total fertility rate in Korea is 1.17 in 2016, the lowest among the OECD members. The decrease in these fertility rate adversely affects the decrease in production population and the growth of national growth. Therefore, the following improvements shall be considered. First, Parental leave is currently a year away, but it needs to be increased, on the level of parental leavel. Also, it is necessary to revise parental leave automatically without having to apply for paternity leave when taking advantage of parental leave. Second, the income replacement rate of parental leave is very urgent Worker’s the income replacement rate is 40% by the employment insurance act article 95. But As the income replacement rate, 40 percent are not enough, which is very poor policy of the wake of the fertility rate. High the income replacement rates are a major factor in raising fertility rate. Thus, a revision of employment insurance act is needed to phase out the income replacement rate. Also, adjustments to both the upper and lower levels should be improved simultaneously to positively affect the fertility rate. Third, confirmation of financial resources should be considered to increase the income replacement rate. Benefits of parental leave are supported in employment insurance in Korea. Unemployment benefits should be used for purposes of unemployment relief purposes, for purposes of the original purpose and It should be considered revision of unemployment benefit, maternity leave benefit, parental leave benefit. It is urgent to improve the fertility rate through active support for the nation's finances. KCI Citation Count: 0